Contribution to the knowledge of antlions of the genus Euroleon Esben-Petersen, 1918 (Neuroptera: Myrmeleontidae) with new records and synonymy - V.A. Krivokhatsky; E.V. Ilyina; I. Kerimova (Кавказский энтомологический бюллетень, 2021)
This work contains a taxonomic and bionomic information about the genus Euroleon Esben-Petersen, 1918 with two currently known species in the Caucasus and their distribution in Dagestan Republic, Russia. A small colony of larvae of the antlion Euroleon parvus Hölzel, 1972 was found in Dagestan near the permanent habitat of Euroleon nostras (Geoffroy in Fourcroy, 1785) on the territory of the Barkhan Sarykum, the part of Dagestan State Nature Reserve. The 2nd instar larva of E. parvus is described for the first time and habitat conditions of larvae of this species are characterized. An evolutionary scenario for the genus Euroleon is proposed. New synonyms are proposed: Euroleon Esben-Petersen, 1918 = Myrmeleo Blanchard, 1845, syn. n. (the type species Formicaleo nostras Geoffroy in Fourcroy, 1785 is designated here), but that senior synonym does not concord with Euroleon in terms of priority (Article 23.7.2 of the International Code of Zoological Nomenclature); Euroleon nostras (Geoffroy in Fourcroy, 1785) (ex Formicaleo) = Myrmeleon formicarium Linnaeus, 1767 sensu Blanchard, 1845, syn. n.; Euroleon coreanus Okamoto, 1926 = Euroleon flavicorpus Wang in Ao, Zhang, Abraham, Wang, 2009, syn. n.